(untitled) - McFarland, Grant (New York, 2006)
Developed from a successful corporate training course, this hands-on learning guide walks readers through every step of microprocessor design. You'll follow a new processor product from initial planning through design to production. In Microprocessor Design, the author converts his real-world design and teaching experience into an easy-to-follow reference employing an on-the-job-training approach to cover: The evolution of microprocessors; Microprocessor design planning; Architecture and microarchitecture; Logic design and circuit design; semiconductor manufacturing and Processor packaging and test
Keywords: Microprocessors,Computer architecture,Mạch vi xử lý,Cấu trúc máy tính; Design and construction,Thiết kế và xây dựng